First Nations' Health, Mental Health, Social, and Emotional Wellbeing - Rhonda Wilson (2024)
In "First Nations' Health, Mental Health, Social, and Emotional Wellbeing," readers are invited to explore contemporary issues surrounding the health, mental health, and social and emotional wellbeing of First Nations peoples. A compilation of the latest in research, scholarship and clinical practices by a wide range of authors (First Nation and Allies) has been curated to support clinicians and students across the health professions to strengthen their knowledge and promote culturally responsive practice.